PELATIHAN MENGATASI COMMUNICATION APPREHENSION DENGAN MENGGUNAKAN LAYANAN BIMBINGAN KELOMPOK (PADA ANAK-ANAK DI PONDOK PESANTREN YATIM ALIF TSALATSA SURAKARTA) - Eko Adi Putro (Lembaga Penelitian dan Pengabdian Masyarakat, 2018)
There are symptoms of children in Alif Tsalatsa Surakarta experienced communication apprehension from the counseling interview conducted by the author to some children in the boarding school is a number of children when chatting with friends, as if the conversation is cornered him and then away from the crowd and choose alone when his friend was just joking. In addition one of the children said that if communicating with his friend even if it was just a casual conversation he felt confused to position himself, if gathered together in a small group between lodgers look worried, depressed from the sweaty hands, and nervous looking confused in starting the conversation and was afraid the topic was unattractive. In addition, if there is a problem with his friend, the student does not dare to express his heart. He prefers silence because when spoken of he is afraid of tipping the problem and afraid if the child is abandoned his friends.The training of group guidance services is able to cope with communication apprehension (In Children In Alif Tsalatsa Surakarta). Method of Implementation in this community service activities is with the provision of services group guidance. by using the game in this activity is in every meeting will discuss the topic of the task of the theme of communication in the process of its activities inserted game put forward by Suwarjo and Eliasa are: a) chain word; b) Our Picture; c) Trips of the Three Disabled; d) Continue my story; e) Standing Together. The Meaning of the Game has to do with the theme presented.Key Words ; Group Guidance, Communication Apprehension